Answer:
(-2, -3)
Step-by-step explanation:
Step 1 - Multiply the second equation by two and add the two rows together
x + 2y = -8
y = 1/2x - 2
x + 2y = -8
2y - x = -4
4y = -12
Step 2 - Divide both sides of the equation by four
4y = -12
4y/ 4 = -12/ 4
y = -3
Step 3 - Substitute the negative three for y in the first equation and simplify
x + 2y = -8
x + 2(-3) = -8
x - 6 = -8
Step 4 - Add six to both sides of the equation
x - 6 = -8
x - 6 + 6 = -8 + 6
x = -2
Therefore, the ordered pair should be (-2, -3).